Cognitive Biases That Shape the Drivers and Barriers to Embracing Green Construction Practices - Purushothaman, Mahesh Babu; Aguas, Angelo Bien (Emerald, 2025)
Purpose The challenges associated with cognitive biases can significantly impact individuals, particularly when making informed decisions about driving and adopting green construction practices. Recognising and approaching these barriers with understanding and empathy is essential, as they often stem from deeply rooted habits and perceptions. This study highlights the drivers and barriers to green building construction practices and identifies the cognitive biases associated with these factors that can aid global project managers, policymakers and construction professionals. Design/methodology/approach A dual systematic literature review was employed to assess academic journal articles published between 2018 and 2023, ensuring the recency of the information and utilising narrative and thematic analysis to conclude. Findings The study’s results reveal the profound influence of cognitive biases on the factors that shape the adoption of green building practices. A total of 95 factors and 71 cognitive biases were identified, providing substantial evidence and information for our study. These findings, presented in tables and a dynamic map, highlight the intricate interrelationships in this context, offering a comprehensive understanding of the subject matter. Research limitations/implications Using a systematic literature review (SLR) as a qualitative research method imposes constraints on accessing the most up-to-date industry knowledge, as it limits the selection of reviewed literature. In addition, the absence of diverse academic databases restricts the availability of valuable and credible sources to support the study. Moreover, focusing solely on English-language resources overlooks relevant references published in other languages. Despite these limitations, strict adherence to journal articles and the Prisma process enhances the credibility and reliability of the paper’s findings. Practical implications The research offers valuable insights for project managers, construction professionals and policymakers, highlighting the cognitive biases that influence decision-making in green building construction. It provides a detailed analysis of the interconnected factors that promote sustainable practices and identifies the challenges that hinder their implementation. Additionally, the study explores how existing beliefs and biases influence the decisions of builders, architects and developers in their pursuit of sustainability. The theoretical implications of our study extend to future research, providing a foundation for exploring the human perspective within the construction industry. Originality/value This paper novelly explores interconnected factors by examining the key drivers that promote sustainable building practices, the barriers that hinder their implementation and the cognitive biases that influence decision-making in this context. It specifically examines the key drivers that promote sustainable building practices, the barriers that hinder their implementation and the cognitive biases that influence decision-making in this context.
Keywords: 12 Built Environment and Design; 33 Built environment and design